2009
DOI: 10.1109/tase.2008.2009088
|View full text |Cite
|
Sign up to set email alerts
|

Control of Drug Administration During Monitored Anesthesia Care

Abstract: Monitored anesthesia care (MAC) is increasingly used to provide patient comfort for diagnostic and minor surgical procedures. The drugs used in this setting can cause profound respiratory depression even in the therapeutic concentration range. Titration to effect suffers from the difficulty to predict adequate analgesia prior to application of a stimulus, making titration to a continuously measurable side effect an attractive alternative. Exploiting the fact that respiratory depression and analgesia occur at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Caruso et al [4] modelled the effect of remifentanil on breathing and showed that their controller maintains CO 2 set point in the presence of disturbances. Gentilini et al [11] proposed a model for the regulation of mean arterial pressure (MAP) and hypnosis with isoflurane-it was observed that controlling both MAP and hypnosis simultaneously with isoflurane was difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Caruso et al [4] modelled the effect of remifentanil on breathing and showed that their controller maintains CO 2 set point in the presence of disturbances. Gentilini et al [11] proposed a model for the regulation of mean arterial pressure (MAP) and hypnosis with isoflurane-it was observed that controlling both MAP and hypnosis simultaneously with isoflurane was difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations demonstrated that Remifentanil concentrations well tolerated in the steady state will cause a clinically significant hypoventilation following bolus administration, confirming the acute risk of bolus administration of fast-acting opioids in spontaneously breathing patients (Caruso et al, 2009;Pattinson et al, 2009). Haemodynamic Effects: Remifentanil induces a dosedependent decrease in heart rate, arterial blood pressure and cardiac output consistent with µ-opioid agonism (Caruso et al, 2009;Mahfouf et al, 2005). Central Nervous System: Remifentanil induces dosedependent changes in relative cerebral blood flow in areas involved in pain processing.…”
Section: Respiratory Effectmentioning
confidence: 77%
“…A fuzzy analgesia control system for induction, maintenance and recovery has been reported in (Schubert et al, 2008), using three variables: heart rate, mean arterial pressure and an index derived from a (modified) standard deviation of the RR-intervals in the electrocardiogram format. Furthermore, a control system, which minimizes the risks associated with delivery of respiratory depressants to spontaneously breathing patients during medical procedures, has been proposed in (Caruso et al, 2009). This has been based on modelling the respiratory depressant effects of Remifentanil by means of pharmacokinetic (PK)-pharmacodynamic (PD) models in (Caruso et al, 2009) provided the transcutaneous monitoring of partial pressure of carbon dioxide in tidal breathing.…”
Section: The Multivariable Paradigm Of Automated Doamentioning
confidence: 99%
See 1 more Smart Citation
“…Automation can benefit a variety of medical applications: surgical robotics [14], remote diagnosis [15], radiation biodosimetry [16],health analytics [17] and monitored anesthesia control [18]. Okamura et al [19] provides a detailed description of recent advances in medical and healthcare robotics.…”
Section: Background and Related Workmentioning
confidence: 99%